Characterization of Neonatal Sepsis in a Tertiary Hospital in Nigeria. (March 2022) - Obadare, T.; Adejuyigbe, E.; Adeyemo, A.; Aboderin, O.
Abstract : Purpose: This study determined epidemiology and microbiological characteristics of neonatal sepsis as well as risk factors for mortality at a tertiary hospital in Southwest Nigeria. Methods & Materials: A Cross-sectional study conducted from December 2017 to April 2019 entailed collection of demographic and clinical data, assay of serum procalcitonin by semi-quantitative kit and blood culture by BACTEC blood culture system. Bacterial isolates were identified by standard biochemical methods. Antibiotic susceptibility testing was by modified Kirby-Bauer method and result interpreted with established guidelines. Phenotypic testing for production of extended-spectrum β-lactamase and carbapenemase was done by standard methods. Genetic determinant of resistance ( mec A, bla TEM, bla SHV, bla CTX bla KPC, bla NDM, and bla OXA) was done by polymerase chain reaction-based protocols. Quantitative variable was expressed as frequencies and mean. Chi Square was used to determine association between variables while logistic regression analysis was done to identify independent risk factors. Results: Of the 763 neonates admitted during the study, 192 were clinically diagnosed sepsis among which 82 (42.7%) had positive blood culture. The commonest isolates were Staphylococcus aureus (42/82), Coagulase negative Staphylococcus spp (17/82), Enterobacter spp (8/82) and Acinectobacter spp (6/82). Of the Staphylococcus aureus and Coagulase negative Staphylococcus spp, 85.7% (36/42) and 52.9% (9/17) were respectively methicillin resistant. Gram-negative bacilli showed high) resistance to ampicillin 81.3% (13/18) and ceftriaxone 75.0% (12/16), and considerable resistance to meropenem (25.0%). There was no resistance to amikacin. Four isolates were ESBL- (mostly bla CTX) and AmpC-β-lactamase-producing. Respiratory rate of ≥60cpm (60/82; p<0.03), reduced movement lethargy/unconsciousness (59/82; p=0.00) and grunting (54/82; p=0.04) were associated with positive blood culture. Independent risks for culture were meconium passage before birth (17/82; p=0.03) and prolonged rupture of membrane ≥ 24hrs (50/82; p=0.01). Independent risks for neonatal mortality were elevated serum pro-calcitonin (68/144; p= 0.03), Gram-negative bacteraemia (9/144; p=0.00) and low birth weight (≤2500g) [9/44; p=0.03]. Conclusion: Aetiology of neonatal sepsis was diverse. There was high resistance to recommended antibiotics by World Health Organization (WHO). Serum procalcitonin prognosticates neonatal sepsis and its utilization should be heightened for improved antibiotic stewardship and better patient outcomes.